Production of High-Octane Number Gasoline from Basra Low Octane-Number Gas Condensate and Ethanol over Modified Zn/ZSM5 Zeolite Catalyst - Mohammed Abdulrazzaq Salim; Usama Akram Saed (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Catalytic transformation of a low-octane number stable gas condensate to high-octane number gasoline (RON: research octane number) is an economically and strategically vital process. In this research, modifying ZSM5 zeolite (80 Si/Al ratio) by impregnation with 2% Zn (Zn/ZSM5) was carried out to increase the selectivity for isomerization and aromatization thereby enhance the octane number. The process was conducted by using stable gas condensate 85 vol% with 15 vol% ethanol in a fixed bed reactor. Zn/ZSM5 and ZSM5 were examined in a pilot scale under different conditions temperature 360-420 °C LHSV1.2-2 h−1, pressure 5 bar. Catalysts were characterized before and after Zn loading using Fourier Transform Infra Red (FT-IR), Brunauer-Emmett-Teller (BET), X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), Field Emission Scanning Electron Microscope (FESEM), Transmission Electron Microscope (TEM), and N2-adsorption. The SEM, FESEM, and TEM have shown that no change in morphology and metal distribution. The XRD and FTIR characterizations revealed the modified catalysts retained their crystallinity after metal impregnation while N2-adsorption isotherm demonstrates no significant change in porosity. The results of Zn/ZSM5 display an optimum result at 420 °C, 1.2 h−1, 5 bar with enhancement of RON from 60.5 to 89 whereas ZSM5 shows RON enhancement from 60.5 to 82. Post Zn loading, PONA test has shown an increase for iso-paraffin from 45.4 to 47.4%, and aromatics from 10.8 to 14. The findings translate the effectiveness of using Zn on ZSM5 for gas condensate – gasoline transformation. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).